Signal-Aware Fraud Detection: A Taxonomy for Sustainable and Lifecycle-Oriented Detection Architectures - Ribeiro, Sara Santedicola; Mendonça, Fabio Lucio Lopes de; Peotta, Laerte (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
Online financial fraud is growing in scale, coordination and operational complexity, challenging detection systems to balance accuracy, interpretability, scalability and computational efficiency. This work proposes a signal-aware perspective for fraud detection centered on the observable evidence generated throughout fraudulent activity. Fraud-relevant signals are organized into temporal, distributional, structural and contextual families, which may be operationalized explicitly, implicitly or through hybrid representations. To contextualize signal emergence, the paper introduces a conceptual fraud lifecycle model that distinguishes strategic and operational reconnaissance activities and highlights the asymmetric observability of fraud across lifecycle stages. Building on this perspective, the paper analyzes how different detection paradigms operationalize signal families and examines the associated trade-offs involving computational complexity, latency, scalability and interpretability. By reframing fraud detection as a process-aware and systems-oriented problem grounded in signal emergence and operationalization, this work contributes towards the design of more explainable, efficient and operationally robust fraud detection systems.